Considerations in biodistribution evaluation of iPSC-derived cell therapy: A pancreatic islet cell case study - Miyu Nakayama; Yuu Moriya; Hikaru Ueno; Takeshi Watanabe; Hideki Hirabayashi; Syunsuke Yamamoto (Molecular Therapy: Methods & Clinical Development)
Induced pluripotent stem cells (iPSCs) have substantial transformative potential in regenerative medicine, enabling tissue repair and restoration. However, their clinical application is limited by tumorigenic risks owing to their pluripotency. Biodistribution studies are crucial for elucidating the fate and tumorigenicity risk of iPSC-derived cell therapy products (CTPs). The lack of standardized biodistribution study protocols has led to inconsistent and unreliable study results, posing difficulties in the drug approval process. Therefore, we conducted a case study on the biodistribution of iPSC-derived pancreatic islet cells to develop a standardized biodistribution assessment protocol for iPSC-derived CTPs. We optimized a droplet digital polymerase chain reaction method targeting human-specific LINE1 sequences and validated its quantitativity for quantification across different tissues using a single calibration curve. We performed a long-term biodistribution study of iPSC-derived pancreatic islet cell in immunodeficient mice to assess biodistribution characteristics, which indicated that they remained localized at the transplantation site for one year, with no migration to other organs, suggesting long-term survival, minimal tumorigenicity risk, and advantages for clinical application. This study provides valuable insights into the standardization of biodistribution protocols for iPSC-derived CTPs.